2021
DOI: 10.1155/2021/5532159
|View full text |Cite
|
Sign up to set email alerts
|

Tibetan Medicines and Tibetan Prescriptions for the Treatment of Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is one of the most serious diseases threatening human health and because of that, it is imperative to look for drugs to tackle it. The Tibetan medicine, a traditional medical system used in China, is currently being the focus of research towards the discovery of new effective drugs against several diseases. Based on the literature survey of Tibetan medicine monographs and drug standards, the Tibetan medicine, and Tibetan prescription used in the traditional Tibetan medical system, here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Tibetan medicinal knowledge of diabetes, which first appeared in the eighth century, was born in the Four Medical Tantras (the classics of Tibetan medicine). The book calls it “jingnisaku disease,” which falls under the category of frequent urination and is caused by a combination of internal and external factors such as uncontrolled diet and irregular daily routines [ 6 , 7 ]. According to color and nature of urine, the Tibetan medical book Eight Branches Essentials puts forward the classification of diabetes and elaborates the diseases that diabetic patients are prone to, which coincides with the idea of various acute and chronic complications in the late stage of diabetes recognized by modern medicine [ 8 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tibetan medicinal knowledge of diabetes, which first appeared in the eighth century, was born in the Four Medical Tantras (the classics of Tibetan medicine). The book calls it “jingnisaku disease,” which falls under the category of frequent urination and is caused by a combination of internal and external factors such as uncontrolled diet and irregular daily routines [ 6 , 7 ]. According to color and nature of urine, the Tibetan medical book Eight Branches Essentials puts forward the classification of diabetes and elaborates the diseases that diabetic patients are prone to, which coincides with the idea of various acute and chronic complications in the late stage of diabetes recognized by modern medicine [ 8 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies on TTM will definitely extend their clinical applications. With a great respect to previously review about TMM for the treatment of DM ( Gao et al, 2021 ), our review presents an updated pharmacological view of TMM for further exploration and application in DM and its complications treatment, which providing broadened understanding of the underlying mechanisms of TMM to find innovative strategies for DM management.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in Tibetan medicine, it is used for the treatment of coronary heart diseases, mountain sickness, strengthening of the spleen and stomach, and multiple other diseases ( Tang et al, 2017 and references therein). In Tibetan medicine, it has been reported as a treatment for diabetes mellitus ( Gao et al, 2021 ). It has also been reported that some subspecies of C. convolvulacea , e.g., subsp.…”
Section: Introductionmentioning
confidence: 99%